UTILIZATION OF PRAGMA-STYLISTICS STRATEGIES IN LEARNING CONTEXT FOR COMMUNICATING GLOBAL PEACE - Nurhadi, Jatmika (Jurnal Politikom Indonesiana, 2017)
Efforts to establish and embed global peace can be started in the context of education. One of them is the use of linguistic strategies used in learning. The linguistic strategy can be a medium to build positive characters of the students. In this situation, language has an important role as it relates to the sociocultural and psychological aspects. These linguistic strategies utilize pragmatics and stylistics markers combined to make permissive (friendly to the human mind) formulation speech acts. This research used a qualitative method with descriptive data presentation. This research will describe the use of stylistics components, such as (1) epizeuxis, (2) parallelism, (3) prolepsis, (4) simile, (5) chiasmus, and (6) positive vs. Negative phrase, and the use of pragmatics component (1) assertives, (2) directives, and (3) expressives speech acts. These linguistic strategies are expected to be used by teachers to form students into agents of peace. Furthermore, these strategies can be used as a guidance in preparing the message of peace that will be distributed around the world. One major implication of the conclusion is using a strategy pragma-stylistic teacher will be easier to invite students to be agents of peace. However, this strategy needs to be aware and accustomed to the structure of the speech delivered well received by students, and the speech will be more permissive.